A graphical theory of social license: applications to climate action, renewable energy and sustainable food production - Scott A. Condie; Corrine M. Condie (Humanities & Social Sciences Communications)
Abstract Concepts such as community attitudes, social influence, social acceptability, social license, and conflict are core elements of macro-sociological theory, as well as being central to contemporary debates across a wide range of contentious environmental issues. While there are clear conceptual linkages, the absence of quantitative definitions and theory has hindered the integration of these concepts and allowed them to be used selectively to advance particular viewpoints. Here we unify these concepts within a novel social license graph that uses attitudinal data to objectively map community interest and the social acceptability of any operation or sector. This approach allows rigorous quantitative assessment of the social performance of management and policy over time. Three contentious environmental issues (climate action, renewable energy, and sustainable food production) have been used to demonstrate how the social license graph can track social acceptability over time and help evaluate management options.